2018
DOI: 10.1590/0001-3765201820160333
|View full text |Cite
|
Sign up to set email alerts
|

Statistical tools application on dextranase production from Pochonia chlamydosporia (VC4) and its application on dextran removal from sugarcane juice

Abstract: The aim of this study was to optimize the dextranase production by fungus Pochonia chlamydosporia (VC4) and evaluate its activity in dextran reduction in sugarcane juice. The effects, over the P. chlamydosporia dextranase production, of different components from the culture medium were analyzed by Plackett-Burman design and central composite design. The response surface was utilized to determine the levels that, among the variables that influence dextranase production, provide higher production of these enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Dextranase and its products are widely used in food, medicine, and other fields. In sugar industry, dextranase can remove dextran to improve production efficiency, yield, and quality of sucrose (Bhatia et al, 2010(Bhatia et al, , 2016Eggleston et al, 2009;Sufiate et al, 2018;Zhao et al, 2021). Dextranase has many applications in the prevention and treatment of dental caries (Jiao et al, 2014;Juntarachot et al, 2020;Lai et al, 2019;Ren et al, 2016).…”
Section: Dextranasementioning
confidence: 99%
“…Dextranase and its products are widely used in food, medicine, and other fields. In sugar industry, dextranase can remove dextran to improve production efficiency, yield, and quality of sucrose (Bhatia et al, 2010(Bhatia et al, , 2016Eggleston et al, 2009;Sufiate et al, 2018;Zhao et al, 2021). Dextranase has many applications in the prevention and treatment of dental caries (Jiao et al, 2014;Juntarachot et al, 2020;Lai et al, 2019;Ren et al, 2016).…”
Section: Dextranasementioning
confidence: 99%
“…Recently, our research group described the first report of dextranase production by the fungus Pochonia chlamydosoporia, a facultative parasite of eggs and female nematodes found in the soil in various regions of the world. This enzyme reduced the dextran content of sugarcane juice by 75%, with 12-h treatment (Sufiate et al 2018).…”
Section: Introductionmentioning
confidence: 95%
“…Given the economic losses of dextran to the sugar industry, much attention has been drawn to hydrolyze and remove dextran in various approaches. A wide range of previous studies suggested that the depolymerization of dextran by dextranase was evaluated as the most appropriate method compared with other physical methods with poor economic feasibility ( Purushe et al, 2012 ; Sufiate et al, 2018a ; Tanoue Batista et al, 2021 ). Consequently, with the rapid development of protein spatial structure analysis ( Chew et al, 2019 ; Sankaran et al, 2019 ; Krishna Koyande et al, 2020 ; Wang et al, 2022 ), it is a burning problem to explore the enzymatic properties and application suitable for sugar processing of dextranase.…”
Section: Introductionmentioning
confidence: 99%